Aggregation‐Induced Emission Boosting the Study of Polymer Science. Issue 16 (1st April 2022) - Ge, Sheng; Wang, Erjing; Li, Jinhua; Tang, Ben Zhong
Abstract: The past one hundred years have witnessed the great development of polymer science. The advancement of polymer science is closely related with the development of characterization techniques and methods, from viscometry in molecular weight determination to advanced techniques including differential scanning calorimetry, nuclear magnetic resonance, and scanning electron microscopy. However, these techniques are normally constrained to tedious sample preparation, high costs, harsh experimental conditions, or ex situ characterization. Fluorescence technology has the merits of high sensitivity and direct visualization. Contrary to conventional aggregation‐causing quenching fluorophores, those dyes with aggregation‐induced emission (AIE) characteristics show high emission efficiency in aggregate states. Based on the restriction of intramolecular motions for AIE properties, the AIE materials are very sensitive to the surrounding microenvironments owing to the twisted propeller‐like structures and therefore offer great potential in the study of polymers. The AIE concept has been successfully used in polymer science and provides a deeper understanding on polymer structure and properties. In this review, the applications of AIEgens in polymer science for visualizing polymerization, glass transition, dissolution, crystallization, gelation, self‐assembly, phase separation, cracking, and self‐healing are exemplified and summarized. Lastly, the challenges and perspectives in the study of polymer science using AIEgens are addressed. Abstract : The aggregation‐induced emission (AIE) concept has been shining light on the polymer's study using fluorescence techniques. In this review, the applications of AIE‐active luminogens for visually tracing the structures and properties of polymers are exemplified and summarized. The challenges and perspectives for AIE utilization in polymer science are addressed.